Foreign portfolio investment and economic growth : an asymmetric cointegration approach. - Duasa, Jarita; Kassim, Salina (International Islamic University, 2009)
The present study attempts to analyze the long-run equilibrium relationship between foreign portfolio investment (FPI) and real Gross Domestic Product (GDP) by cointegration tests assuming asymmetric adjustment. Following Enders and Siklos (2001), the Engle-Granger two-step cointegration test is expanding to incorporate an asymmetric error correction term. It is found that there exists asymmetric cointegration between net foreign portfolio investment and real GDP, when momentum-threshold autoregressive (M-TAR) model is conducted. However, the asymmetric cointegration is not existence using threshold autoregressive (TAR) model. From estimation of M-TAR error-correction model, the adjustment back to equilibrium is more significant following relative increase in FPI (above long-run value). However, the adjustment is diverted from equilibrium following relative decrease in FPI (below long-run value).